KORELASI PERGAULAN TEMAN SEBAYA DENGAN AKTIVITAS BELAJAR KELAS VIISMP NEGERI 2 SUNGAI RAYA - Mamat Heriyadi; M Asrori; Luhur Wicaksono (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine the correlations of peer relationships with learning activities of students in class VII of Sungai Raya 2Junior High School. The method used was descriptive method and the form of the study was the study of relationships. The population in this study was 254 students and the sample was 52 students. Data collection techniques in this study were indirect communication and data collection tools used are questionnaires, while data analysis techniques use percentage formulas and product moment correlations. Based on the results of this study indicated that peer ralationships were the most dominant class VII of Sungai Raya 2 Junior High School are cliques achieve a score of 73% with the category “High”. While the most dominant learning activities in class VII of Sungai Raya 2Junior High Schoolwere writing activities. Who achieved a score of 64% with the “Medium” category. Based on the results of the study using pearson’s hiererchical correlation method, the correlation coefficient correlation rs=0,616. This indicateed a correlation. It can be concluded that in this study “There is a relationship between peer relationships with learning activities of students in class VII of Sungai Raya 2Junior High School”. Keywords: Learning Activities,Peer Relationships